A method for detecting metallic foreign matter in organic polymers and its application

By using concentrated sulfuric acid pretreatment and calcination treatment in lithium-ion battery separator detection, the problems of low detection results and safety hazards are solved, and more accurate detection of metal foreign matter and safety performance are achieved.

CN114689568BActive Publication Date: 2025-01-07SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210330577.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-30
Publication Date
2025-01-07
Estimated Expiration
2042-03-30

AI Technical Summary

Technical Problem

The existing metal foreign body detection methods in lithium-ion battery separators have problems with low detection results and safety risks, especially when the metal elements of fine particles lead to low results during the calcination process, and improper calcination temperature control may lead to the risk of fire.

Method used

The samples to be tested are pretreated and calcined with concentrated sulfuric acid, and the complete removal of metal foreign matter is ensured through the carbonization and ashing process, and elemental testing is carried out using ICP-OES or AAS to improve the accuracy and safety of the detection results.

Benefits of technology

Through concentrated sulfuric acid pretreatment and high-temperature roasting, the content of metal foreign matter in the sample to be tested can be more accurately determined, the deviation of the detection result can be reduced, and the risk of open fire can be effectively reduced, and the safety and accuracy of the detection can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114689568B_ABST
    Figure CN114689568B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of analytical testing technology, and specifically relates to a detection method and application of metal foreign matter in an organic polymer. The technical solution provided by the present invention is to first pre-treat the sample to be tested with concentrated sulfuric acid, and then perform roasting and ashing, and finally test it using inductively coupled plasma emission spectroscopy (ICP‑OES) or atomic absorption spectroscopy (AAS). The present invention uses sulfuric acid for carbonization to partially dissolve the organic polymer, which can help the sample to be ashed more easily during the subsequent roasting process. During the roasting and ashing process, concentrated sulfuric acid is still left in the sample, which can prevent the ashing fine particles from flying away. In addition, concentrated sulfuric acid can fix the metal elements, improve the accuracy of the test results, and at the same time, can avoid the safety risks caused by open flames.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of analysis and testing, and specifically relates to a method for detecting metallic foreign matter in an organic polymer and an application thereof. Background Art

[0002] Lithium-ion batteries are widely used in mobile phones, tablet computers and power equipment due to their high energy density and long cycle life. The structure of lithium-ion batteries generally includes positive electrode, separator, negative electrode, electrolyte and shell.

[0003] Lithium-ion battery binders are important components in the positive electrode slurry. They can bind the positive electrode particles together and tightly bind the formed positive electrode slurry and aluminum foil together. Excellent binders are not only conducive to improving the energy density of the battery, but also have an important impact on the electrochemical performance of the battery. If the binder contains metal impurities, these metal impurities will accumulate at the negative electrode during the charge and discharge process, causing the diaphragm to be punctured, which in turn causes the battery to short-circuit, causing serious safety risks. Therefore, strictly controlling the content of metal impurities in the binder is of great significance to improving the safety and electrochemical performance of lithium-ion batteries.

[0004] For example, the prior art discloses a method for testing the content of metallic foreign matter in a lithium-ion battery separator, the method comprising: (1) subjecting the separator to a first-stage calcination to remove organic substances on the surface of the separator; (2) subjecting the calcined product obtained in step (1) to a second-stage calcination to remove organic substances inside the separator; and (3) subjecting the ash obtained in step (2) to an ICP test to obtain the content of metallic foreign matter in the lithium-ion battery separator.

[0005] The main problems with the above testing method are: 1. During the calcination process, the sample will be heated to produce fine particles. Due to its light weight, the particles will diffuse in the hot air flow of the calcination device, but these fine particles also contain metal elements, so the final test results will be low; 2. The calcination method will lead to insufficient removal of organic matter, and subsequent treatment will not be able to dissolve all the metal elements in the sample phase, which will also lead to low results; 3. If the temperature is not well controlled during the calcination process, there will be a risk of open flames, posing a safety hazard. Summary of the invention

[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the detection method of metal foreign matter in organic polymer materials in the prior art, such as low detection results and safety hazards in the operation process, thereby providing a detection method and application of metal foreign matter in organic polymers.

[0007] The technical solution provided by the present invention is to first pretreat the sample to be tested with concentrated sulfuric acid, then perform roasting and ashing treatment, and finally perform ICP-OES (AAS can also be used) testing. By utilizing the dual effects of the added concentrated sulfuric acid in the pretreatment and ashing process, the content of metallic foreign matter in the sample to be tested can be determined more accurately, which is of great significance to improving the safety performance and electrochemical performance of lithium-ion batteries.

[0008] To this end, the present invention provides the following technical solutions:

[0009] The present invention provides a method for detecting metal foreign matter in an organic polymer, comprising the following steps:

[0010] S1, carbonizing the sample to be tested with concentrated sulfuric acid;

[0011] S2, calcining the sample after carbonization to make the sample ash;

[0012] S3, digesting the ashing sample with acid to obtain a test solution;

[0013] S4, performing element test on the solution to be tested to obtain the content of metallic foreign matter in the sample to be tested.

[0014] Optionally, elemental testing is performed using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) or Atomic Absorption Spectroscopy (AAS).

[0015] Optionally, the carbonization treatment is carried out at a temperature of 200-230° C. and for a time of 25-30 min.

[0016] Optionally, in step S1, the amount of concentrated sulfuric acid used is (2-3) mL / g based on the mass of the sample to be tested.

[0017] Optionally, the mass concentration of concentrated sulfuric acid in step S1 is above 70%;

[0018] Optionally, the mass concentration of the concentrated sulfuric acid is 80%-98.3%.

[0019] Optionally, the calcination temperature in step S2 is 400-900° C., and the calcination time is 3-8 hours.

[0020] Optionally, the calcination operation is to increase the temperature to 400-450°C at a rate of 6-7°C / min, calcining for 1-2h, and then increase the temperature to 800-900°C at a rate of 3-4°C / min, calcining for 2-6h.

[0021] Optionally, the mass concentration of the acid in step S3 is 36-38%;

[0022] And / or, based on the mass of the sample to be tested, the amount of the acid used is (5-6) mL / g.

[0023] Optionally, the acid in step S3 is at least one of hydrochloric acid, nitric acid, and sulfuric acid.

[0024] Optionally, the digestion operation temperature in step S3 is 180-200° C. and the time is 15-20 min.

[0025] The sample to be tested in the present invention can be any organic polymer raw material.

[0026] The present invention also provides an application of the above-mentioned method for detecting metal foreign matter in an organic polymer in the detection of a lithium ion battery binder or a lithium ion battery separator.

[0027] Typically, but not limited to, the lithium-ion battery binder is polyvinylidene fluoride, and the lithium-ion battery separator is polyethylene.

[0028] The principle of the technical solution of the present invention is explained below by taking polyvinylidene fluoride as an example: polyvinylidene fluoride is a highly non-reactive thermoplastic fluorine-containing polymer, the CF bond energy in the chemical structure is large and F can form a stable structure with H (for other organic polymers, there are other relatively stable structures), which makes polyvinylidene fluoride a high-strength, high-stability substance, but also leads to the problem that polyvinylidene fluoride is difficult to digest when doing element testing. The present invention uses concentrated sulfuric acid to open the stable structure of polyvinylidene fluoride and partially dissolve it, and then decomposes the polyvinylidene fluoride by high-temperature roasting, and the C, F, and H elements react to become gas molecules and fly away, and the remaining metal foreign matter can be completely retained in the crucible because it cannot be gasified. In this way, the C, F, and H elements in the highly stable polyvinylidene fluoride can be removed by the sulfuric acid-ashing method, leaving the easily digestible metal foreign matter, and the measured result will be more accurate.

[0029] Typically, the operating procedures and process conditions of the detection method provided by the present invention can be as follows:

[0030] (1) Cleaning of platinum crucible: Use a 30 mL platinum crucible and lid. Soak it in dilute hydrochloric acid or dilute nitric acid and heat it at 120°C for 30 min before use to remove impurities on the platinum crucible. Then wash it three times with ultrapure water and dry it in a 75°C forced air drying oven for 2 h.

[0031] (2) Constant weight of platinum crucible: Place the cleaned platinum crucible and lid into a muffle furnace and calcine at 800°C for 2 h. Take it out and place it in a desiccator. After cooling to room temperature, weigh it and record the mass M1. Repeat the previous steps and record the mass M2. When the masses of M1 and M2 are consistent, proceed to the next step (consistent masses mean that the error of the two weighings is within 3 mg). If not, repeat the above steps until the masses are consistent.

[0032] (3) Sample weighing: Use a 1 / 10,000 balance to weigh 1.0000 g of sample and place it in a platinum crucible. Record the weighed mass and mark the sample number.

[0033] (4) Pretreatment with concentrated sulfuric acid: Place the platinum crucible containing the sample on a tin foil-covered hot plate, add 2-3 mL of concentrated sulfuric acid, and heat at 230 °C until the polyvinylidene fluoride sample turns completely black. Remove the crucible and cool to room temperature.

[0034] (5) Muffle furnace ashing: Place the platinum crucible in a muffle furnace, heat it to 400 °C within 1 h, keep it at that temperature for 1 h, then heat it to 800 °C within 2 h, and keep it at that temperature for 2 h.

[0035] (6) Dissolution with hydrochloric acid - volume adjustment: After the ashing is completed, take out the crucible and place it in a dryer to cool to room temperature. Then, add 5 mL of hydrochloric acid to a platinum crucible, place it on a hot plate with tin foil, heat it at 180°C for 15 min, cool it to room temperature, and pour the acid solution in the platinum crucible into a 50 mL volumetric flask to adjust the volume (rinse the platinum crucible three times to completely rinse out the acid solution).

[0036] (7) Elemental testing: Use ICP-OES (or AAS) to test the above solution to obtain accurate results of metal foreign matter.

[0037] The technical solution of the present invention has the following advantages:

[0038] The detection method of metal foreign matter in organic polymer provided by the present invention comprises the following steps: S1, carbonizing the sample to be tested with concentrated sulfuric acid; S2, calcining the sample after carbonization to ashed the sample; S3, digesting the ashed sample with acid to obtain a solution to be tested; S4, performing element test on the solution to be tested to obtain the content of metal foreign matter in the sample to be tested. Compared with the prior art, the detection method provided by the present invention can improve the accuracy of the test results and reduce the safety risks of organic polymers caused by open flames by adding concentrated sulfuric acid to the sample to be tested. Specifically, using sulfuric acid for carbonization to partially dissolve the organic polymer can help the sample to be ashed more easily during the subsequent calcination process. In the process of slowly heating to 400°C, the acid mist formed by concentrated sulfuric acid can prevent the fine particles of ashing from flying away, fix the metal elements in the calcination container, and further ashed the sample at this temperature to improve the accuracy of the detection results.

[0039] The method for detecting metallic foreign matter in an organic polymer provided by the present invention can achieve a complete ashing effect on the sample by limiting the calcination temperature and time in step S2.

[0040] The method for detecting metallic foreign matter in an organic polymer provided by the present invention can dissolve the metallic impurities in the sample more thoroughly by limiting the digestion temperature and time in step S3. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 The present invention provides a flow chart of a method for detecting metallic foreign matter in an organic polymer. DETAILED DESCRIPTION

[0043] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0044] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0045] In order to ensure the comparability of data, the sources of the polyvinylidene fluoride and polyethylene samples used in the following examples and comparative examples are the same.

[0046] Example 1

[0047] A method for detecting metallic foreign matter in an organic polymer, the specific operation procedures and process conditions are as follows:

[0048] (1) Cleaning of platinum crucible: Use a 30 mL platinum crucible and lid. Before use, soak it in dilute hydrochloric acid (10 wt%) and heat it at 120°C for 30 min to remove impurities on the platinum crucible. Then, wash it three times with ultrapure water and dry it in a 75°C forced air drying oven for 2 h.

[0049] (2) Constant weight of platinum crucible: Place the cleaned platinum crucible and lid into a muffle furnace and calcine at 800°C for 2 h. Take it out and place it in a desiccator. After cooling to room temperature, weigh it and record the mass M1. Repeat the previous steps and record the mass M2. When the masses of M1 and M2 are consistent, proceed to the next step (consistent masses mean that the error of the two weighings is within 3 mg, the same below). If not, repeat the above steps until the masses are consistent.

[0050] (3) Sample weighing: Use a 1 / 10,000 balance to weigh 1.0015 g of polyvinylidene fluoride (model LBG, Arkema, the same below) sample and place it in a platinum crucible. Record the weighed mass and mark the sample number.

[0051] (4) Pretreatment with concentrated sulfuric acid: Place the platinum crucible containing the sample on a tin foil-covered hot plate, add 2.1 mL of concentrated sulfuric acid (98.3 wt %), heat at 200 °C for 30 min until the polyvinylidene fluoride sample turns completely black, remove and cool to room temperature.

[0052] (5) Muffle furnace ashing: Place the platinum crucible in a muffle furnace, heat it to 400 °C within 1 h, keep it at that temperature for 1 h, then heat it to 800 °C within 2 h, and keep it at that temperature for 2 h.

[0053] (6) Dissolution with hydrochloric acid - constant volume: After the ashing is completed, take out and place in a desiccator to cool to room temperature, add 5.1 mL of hydrochloric acid (37.5 wt %) to a platinum crucible, place on a hot plate with tin foil, heat at 180° C. for 15 min, cool to room temperature, and pour the acid solution in the platinum crucible into a 50 mL volumetric flask to constant volume (rinse the platinum crucible three times to completely rinse off the acid solution).

[0054] (7) ICP-OES test: The above solution was tested using ICP-OES, with the operating parameters of argon gas: 0.3 L / min, atomization chamber flow rate: 0.6 L / min, RF power: 1350 W. After testing, the content of metal foreign matter in the sample to be tested is as follows:

[0055] Element Fe (μg / g) Zn (μg / g) Ni (μg / g) Cr (μg / g) Cu (μg / g) Result 1.1 1.1 1.6 1.4 1.3

[0056] Example 2

[0057] A method for detecting metallic foreign matter in an organic polymer, the specific operation procedures and process conditions are as follows:

[0058] (1) Cleaning of platinum crucible: Use a 30 mL platinum crucible and lid. Before use, soak it in dilute hydrochloric acid (10 wt%) and heat it at 120°C for 30 min to remove impurities on the platinum crucible. Then, wash it three times with ultrapure water and dry it in a 75°C forced air drying oven for 2 h.

[0059] (2) Constant weight of platinum crucible: Place the cleaned platinum crucible and lid into a muffle furnace and calcine at 800°C for 2 h. Take it out and place it in a desiccator. After cooling to room temperature, weigh it and record the mass M1. Repeat the previous steps and record the mass M2. When the masses of M1 and M2 are consistent, proceed to the next step. If not, repeat the above steps until the masses are consistent.

[0060] (3) Sample weighing: Use a 1 / 10,000 balance to weigh 1.0009 g of polyvinylidene fluoride sample and place it in a platinum crucible. Record the weighed mass and mark the sample number.

[0061] (4) Pretreatment with concentrated sulfuric acid: Place the platinum crucible containing the sample on a tin foil-covered hot plate, add 3 mL of concentrated sulfuric acid (98.3 wt %), heat at 230 °C for 25 min until the polyvinylidene fluoride sample turns completely black, remove and cool to room temperature.

[0062] (5) Muffle furnace ashing: Place the platinum crucible in a muffle furnace, heat it to 400 °C within 1 h, keep it at that temperature for 1 h, then heat it to 800 °C within 2 h, and keep it at that temperature for 2 h.

[0063] (6) Dissolution with hydrochloric acid - constant volume: After the ashing is completed, take out and place in a desiccator to cool to room temperature, add 6 mL of hydrochloric acid (37 wt %) to a platinum crucible, place on a hot plate with tin foil, heat at 180 ° C for 15 min, cool to room temperature, and pour the acid solution in the platinum crucible into a 50 mL volumetric flask to constant volume (rinse the platinum crucible three times to completely rinse off the acid solution).

[0064] (7) ICP-OES test: The above solution was tested using ICP-OES, with the operating parameters of argon gas: 0.3 L / min, atomization chamber flow rate: 0.6 L / min, RF power: 1350 W. After testing, the content of metal foreign matter in the sample to be tested is as follows:

[0065] Element Fe (μg / g) Zn (μg / g) Ni (μg / g) Cr (μg / g) Cu (μg / g) Result 1.1 1.2 1.6 1.4 1.3

[0066] Example 3

[0067] A method for detecting metallic foreign matter in an organic polymer, the specific operation procedures and process conditions are as follows:

[0068] (1) Cleaning of platinum crucible: Use a 30 mL platinum crucible and lid. Before use, soak it in dilute hydrochloric acid (10 wt%) and heat it at 120°C for 30 min to remove impurities on the platinum crucible. Then, wash it three times with ultrapure water and dry it in a 75°C forced air drying oven for 2 h.

[0069] (2) Constant weight of platinum crucible: Place the cleaned platinum crucible and lid into a muffle furnace and calcine at 800°C for 2 h. Take it out and place it in a desiccator. After cooling to room temperature, weigh it and record the mass M1. Repeat the previous steps and record the mass M2. When the masses of M1 and M2 are consistent, proceed to the next step. If not, repeat the above steps until the masses are consistent.

[0070] (3) Sample weighing: Use a 1 / 10,000 balance to weigh 1.0012 g of polyvinylidene fluoride sample and place it in a platinum crucible. Record the weighed mass and mark the sample number.

[0071] (4) Pretreatment with concentrated sulfuric acid: Place the platinum crucible containing the sample on a tin foil-covered hot plate, add 2.5 mL of concentrated sulfuric acid (80 wt %), heat at 230 °C for 25 min until the polyvinylidene fluoride sample turns completely black, remove and cool to room temperature.

[0072] (5) Muffle furnace ashing: Place the platinum crucible in a muffle furnace, heat it to 450 °C within 1 h, keep it at that temperature for 1 h, then heat it to 900 °C within 2 h, and keep it at that temperature for 2 h.

[0073] (6) Dissolution with hydrochloric acid - constant volume: After the ashing is completed, take out and place in a desiccator to cool to room temperature, add 5.5 mL of hydrochloric acid (37 wt %) into a platinum crucible, place it on a hot plate with tin foil, heat at 180° C. for 15 min, cool to room temperature, and pour the acid solution in the platinum crucible into a 50 mL volumetric flask to constant volume (rinse the platinum crucible three times to completely rinse off the acid solution).

[0074] (7) ICP-OES test: The above solution was tested using ICP-OES, with the operating parameters of argon gas: 0.3 L / min, atomization chamber flow rate: 0.6 L / min, RF power: 1350 W. After testing, the content of metal foreign matter in the sample to be tested is as follows:

[0075] Element Fe (μg / g) Zn (μg / g) Ni (μg / g) Cr (μg / g) Cu (μg / g) Result 1.1 1.1 1.6 1.4 1.4

[0076] Example 4

[0077] A method for detecting metallic foreign matter in an organic polymer, the specific operation procedures and process conditions are as follows:

[0078] (1) Cleaning of platinum crucible: Use a 30 mL platinum crucible and lid. Before use, soak it in dilute hydrochloric acid (10 wt%) and heat it at 120°C for 30 min to remove impurities on the platinum crucible. Then, wash it three times with ultrapure water and dry it in a 75°C forced air drying oven for 2 h.

[0079] (2) Constant weight of platinum crucible: Place the cleaned platinum crucible and lid into a muffle furnace and calcine at 800°C for 2 h. Take it out and place it in a desiccator. After cooling to room temperature, weigh it and record the mass M1. Repeat the previous steps and record the mass M2. When the masses of M1 and M2 are consistent, proceed to the next step. If not, repeat the above steps until the masses are consistent.

[0080] (3) Sample weighing: Use a 1 / 10,000 balance to weigh 1.0003 g of polyethylene (provided by the manufacturer Enjie) sample and place it in a platinum crucible. Record the weighed mass and mark the sample number.

[0081] (4) Pretreatment with concentrated sulfuric acid: Place the platinum crucible containing the sample on a tin foil-covered hot plate, add 2.3 mL of concentrated sulfuric acid (98.3 wt %), heat at 230 °C for 28 min until the polyvinylidene fluoride sample turns completely black, remove and cool to room temperature.

[0082] (5) Muffle furnace ashing: Place the platinum crucible in a muffle furnace, heat it to 400 °C within 1 h, keep it at that temperature for 1 h, then heat it to 800 °C within 2 h, and keep it at that temperature for 2 h.

[0083] (6) Dissolution with hydrochloric acid - constant volume: After the ashing is completed, take out and place in a desiccator to cool to room temperature, add 5.5 mL of hydrochloric acid (37 wt %) into a platinum crucible, place it on a hot plate with tin foil, heat at 180° C. for 15 min, cool to room temperature, and pour the acid solution in the platinum crucible into a 50 mL volumetric flask to constant volume (rinse the platinum crucible three times to completely rinse off the acid solution).

[0084] (7) ICP-OES test: The above solution was tested using ICP-OES, with the operating parameters of argon gas: 0.3 L / min, atomization chamber flow rate: 0.6 L / min, RF power: 1350 W. After testing, the content of metal foreign matter in the sample to be tested is as follows:

[0085]

[0086]

[0087] Example 5

[0088] A method for detecting metallic foreign matter in an organic polymer, the specific operation procedures and process conditions are as follows:

[0089] (1) Cleaning of platinum crucible: Use a 30 mL platinum crucible and lid. Before use, soak it in dilute hydrochloric acid (10 wt%) and heat it at 120°C for 30 min to remove impurities on the platinum crucible. Then, wash it three times with ultrapure water and dry it in a 75°C forced air drying oven for 2 h.

[0090] (2) Constant weight of platinum crucible: Place the cleaned platinum crucible and lid into a muffle furnace and calcine at 800°C for 2 h. Take it out and place it in a desiccator. After cooling to room temperature, weigh it and record the mass M1. Repeat the previous steps and record the mass M2. When the masses of M1 and M2 are consistent, proceed to the next step. If not, repeat the above steps until the masses are consistent.

[0091] (3) Sample weighing: Use a 1 / 10,000 balance to weigh 1.0013 g of polyvinylidene fluoride sample and place it in a platinum crucible. Record the weighed mass and mark the sample number.

[0092] (4) Pretreatment with concentrated sulfuric acid: Place the platinum crucible containing the sample on a tin foil-covered hot plate, add 2.5 mL of concentrated sulfuric acid (98.3 wt %), heat at 230 °C for 28 min until the polyvinylidene fluoride sample turns completely black, remove and cool to room temperature.

[0093] (5) Muffle furnace ashing: Place the platinum crucible in a muffle furnace, heat it to 400 °C within 1 h, keep it at that temperature for 1 h, then heat it to 800 °C within 2 h, and keep it at that temperature for 2 h.

[0094] (6) Dissolution with hydrochloric acid - constant volume: After the ashing is completed, take out and place in a desiccator to cool to room temperature, add 5.8 mL of hydrochloric acid (37 wt %) into a platinum crucible, place on a hot plate with tin foil, heat at 180° C. for 15 min, cool to room temperature, and pour the acid solution in the platinum crucible into a 50 mL volumetric flask to constant volume (rinse the platinum crucible three times to completely rinse off the acid solution).

[0095] (7) AAS test: The above solution was tested using AAS. After testing, the content of metal foreign matter in the sample to be tested is as follows:

[0096] Element Fe (μg / g) Zn (μg / g) Ni (μg / g) Cr (μg / g) Cu (μg / g) Result 1.1 1.1 1.6 1.4 1.3

[0097] Comparative Example 1

[0098] A method for detecting metallic foreign matter in an organic polymer, the specific operation procedures and process conditions are as follows:

[0099] (1) Cleaning of platinum crucible: Use a 30 mL platinum crucible and lid. Before use, soak it in dilute hydrochloric acid (10 wt%) and heat it at 120°C for 30 min to remove impurities on the platinum crucible. Then, wash it three times with ultrapure water and dry it in a 75°C forced air drying oven for 2 h.

[0100] (2) Constant weight of platinum crucible: Place the cleaned platinum crucible and lid into a muffle furnace and calcine at 800°C for 2 h. Take it out and place it in a desiccator. After cooling to room temperature, weigh it and record the mass M1. Repeat the previous steps and record the mass M2. When the masses of M1 and M2 are consistent, proceed to the next step. If not, repeat the above steps until the masses are consistent.

[0101] (3) Sample weighing: Use a 1 / 10,000 balance to weigh 1.0011 g of polyvinylidene fluoride sample and place it in a platinum crucible. Record the weighed mass and mark the sample number.

[0102] (4) Muffle furnace ashing: Place the platinum crucible in a muffle furnace, heat it to 400 °C within 1 h, keep it at that temperature for 1 h, then heat it to 800 °C within 2 h, and keep it at that temperature for 2 h.

[0103] (5) Dissolution with hydrochloric acid - constant volume: After the ashing is completed, take out and place in a desiccator to cool to room temperature, add 5.1 mL of hydrochloric acid (37 wt %) into a platinum crucible, place on a hot plate with tin foil, heat at 180°C for 15 min, cool to room temperature, and pour the acid solution in the platinum crucible into a 50 mL volumetric flask to constant volume (rinse the platinum crucible three times to completely rinse off the acid solution).

[0104] (6) ICP-OES test: The above solution was tested using ICP-OES, with the operating parameters of argon gas: 0.3 L / min, atomization chamber flow rate: 0.6 L / min, RF power: 1350 W. After testing, the content of metal foreign matter in the sample to be tested was:

[0105] Element Fe (μg / g) Zn (μg / g) Ni (μg / g) Cr (μg / g) Cu (μg / g) Result 0.2 0.4 0.5 0.9 0.4

[0106] Comparative Example 2

[0107] A method for detecting metallic foreign matter in an organic polymer, the specific operation procedures and process conditions are as follows:

[0108] (1) Cleaning of platinum crucible: Use a 30 mL platinum crucible and lid. Before use, soak it in dilute hydrochloric acid (10 wt%) and heat it at 120°C for 30 min to remove impurities on the platinum crucible. Then, wash it three times with ultrapure water and dry it in a 75°C forced air drying oven for 2 h.

[0109] (2) Constant weight of platinum crucible: Place the cleaned platinum crucible and lid into a muffle furnace and calcine at 800°C for 2 h. Take it out and place it in a desiccator. After cooling to room temperature, weigh it and record the mass M1. Repeat the previous steps and record the mass M2. When the masses of M1 and M2 are consistent, proceed to the next step. If not, repeat the above steps until the masses are consistent.

[0110] (3) Sample weighing: Use a 1 / 10,000 balance to weigh 1.0006 polyvinylidene fluoride sample and place it in a platinum crucible. Record the weighed mass and mark the sample number.

[0111] (4) Muffle furnace ashing: Place the platinum crucible in a muffle furnace, heat it to 400 °C within 1 h, keep it at this temperature for 2 h, then heat it to 800 °C within 2 h, and keep it at this temperature for 3 h.

[0112] (5) Dissolution with hydrochloric acid - constant volume: After the ashing is completed, take out and place in a desiccator to cool to room temperature, add 5.1 mL of hydrochloric acid (37 wt %) into a platinum crucible, place on a hot plate with tin foil, heat at 180°C for 15 min, cool to room temperature, and pour the acid solution in the platinum crucible into a 50 mL volumetric flask to constant volume (rinse the platinum crucible three times to completely rinse off the acid solution).

[0113] (6) ICP-OES test: The above solution was tested using ICP-OES, with the operating parameters of argon gas: 0.3 L / min, atomization chamber flow rate: 0.6 L / min, RF power: 1350 W. After testing, the content of metal foreign matter in the sample to be tested is as follows:

[0114] Element Fe (μg / g) Zn (μg / g) Ni (μg / g) Cr (μg / g) Cu (μg / g) Result 0.5 0.8 0.9 1.2 0.7

[0115] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for detecting metallic foreign matter in an organic polymer, characterized in that: The steps include: S1, carbonizing the sample to be tested with concentrated sulfuric acid at a temperature of 200-230°C; S2, calcining the sample after carbonization treatment to make the sample ash; the calcination operation is to increase the temperature to 400-450°C at a rate of 6-7°C / min, calcining for 1-2h, and then increasing the temperature to 800-900°C at a rate of 3-4°C / min, calcining for 2-6h; S3, digesting the ashing sample with acid to obtain a test solution; S4, performing element test on the solution to be tested to obtain the content of metallic foreign matter in the sample to be tested.

2. The method for detecting metallic foreign matter in organic polymers according to claim 1, characterized in that: The carbonization treatment time is 25-30 minutes.

3. The method for detecting metallic foreign matter in organic polymers according to claim 1, characterized in that: In step S1, based on the mass of the sample to be tested, the amount of concentrated sulfuric acid used is (2-3) mL / g.

4. The method for detecting metallic foreign matter in an organic polymer according to any one of claims 1 to 3, characterized in that: The mass concentration of concentrated sulfuric acid in step S1 is above 70%.

5. The method for detecting metallic foreign matter in organic polymers according to claim 4, characterized in that: The mass concentration of the concentrated sulfuric acid is 80%-98.3%.

6. The method for detecting metallic foreign matter in organic polymers according to claim 1, characterized in that: The mass concentration of the acid in step S3 is 36-38%; and / or, based on the mass of the sample to be tested, the amount of the acid used is (5-6) mL / g; And / or, the acid in step S3 is at least one of hydrochloric acid, nitric acid and sulfuric acid.

7. The method for detecting metallic foreign matter in organic polymers according to claim 1, characterized in that: Elemental testing was performed using inductively coupled plasma optical emission spectroscopy or atomic absorption spectroscopy.

8. The method for detecting metallic foreign matter in an organic polymer according to claim 6 or 7, characterized in that: The digestion operation temperature in step S3 is 180-200° C. and the time is 15-20 minutes.

9. Use of the method for detecting metallic foreign matter in an organic polymer according to any one of claims 1 to 8 in the detection of lithium ion battery binders or lithium ion battery separators.

Citation Information

Patent Citations

  • A method for determining proton exchange film fuel cell film electrode platinum loading

    CN101055254A

  • Method for recycling valuable metals of waste lithium ion batteries

    CN113174486A

  • Method for testing content of metal foreign matters in lithium ion battery diaphragm

    CN114136954A